Treatment of venous ulcers with fibrin sealant derived from snake venom - Gatti, M. A. N.; Vieira, L. M.; Barraviera, Benedito [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Venous ulcers of the lower limbs complicated by infection or chronicity represent a serious public health problem. The elevated number of those afflicted burdens the health services, interferes in quality of life and causes absenteeism. Although there are 2,500 items on the market, ranging from the simplest dressing up to the most complex types of dressing, treatment remains a challenge. Among the substances used, fibrin sealant is the one that promotes diminution of bacterial colonization and of edema, controls hemorrhaging, alters the pain threshold by protecting the nerve endings, hydrates the wound bed and forms granulation tissue that favors healing. Its disadvantages include higher cost and utilization of human fibrinogen that can transmit infectious diseases. The Center for the Study of Venoms and Venomous Animals (CEVAP) at São Paulo State University (UNESP) developed a new sealant made up of fibrinogen extracted from large animals and from an enzyme obtained from snake venom. The present study, developed in the Health Education Clinic (CEPS) of Sacred Heart University (USC) aimed to evaluate the effect of the new sealant on the healing process of venous ulcers in 24 adult patients, seven of whom were male and 17 female. Two study groups were formed as follows: Group 1 (G1) - control group of 11 patients treated with essential fatty acid (EFA) and Unna's boot, and Group 2 (G2) - 13 patients treated with essential fatty acid (EFA), fibrin sealant and Unna's boot. The follow-up lasted eight weeks and the sealant was applied at only the first and fourth weeks. The results showed that Group 2 presented worse lesion conditions as to healing, but, when comparing the two groups, it was noteworthy that the the sealant was effective in healing venous ulcers. There is evidence that the new sealant is recommended for leg ulcers with the following advantages: ease of application, preparation of the wound bed, diminution of pain and a higher number of discharges in the eighth week. More important, other positive characteristics are non-transmission of infectious diseases, absence of adverse reactions, and economic advantage of being produced by Brazilian technology. Finally, it is suggested that the weekly application of sealant, for at least eight weeks, could improve the healing process and consequently life quality.
Keywords: fibrin sealant; healing; wounds; venous ulcers